2010
DOI: 10.1111/j.1365-2141.2010.08284.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of toll‐like receptors in multiple myeloma patients: toll‐like receptor ligands promote multiple myeloma cell growth and survival via activation of nuclear factor‐κB

Abstract: SummaryToll like receptors (TLRs) are the major agents for innate immunity that recognize invading microbial products and regulate the growth of normal and malignant human B lymphocytes. Multiple myeloma (MM) is a clonal plasma cell malignancy, though the regulatory role of TLRs in MM plasma cells has been reported, the molecular mechanism remains unclear. We first compared the transcripts of TLR1 to TLR10 in MM patients and healthy donors and found that TLR2, ‐4 and ‐9 transcripts were higher in bone marrow m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 44 publications
1
44
0
3
Order By: Relevance
“…Due to the pivotal role of TLRs in immune responses to pathogens, substantial research has been carried out with the aim of understanding the function and biological importance of TLRs on immune cells. However, TLRs are also expressed on many kinds of tumors, such as on melanoma, brain tumor and colon tumor cells [4][5][6][7][8]. Preliminary evidence has suggested that TLRs expressed on tumor cells may play an important role in tumor development.…”
Section: Introductionmentioning
confidence: 97%
“…Due to the pivotal role of TLRs in immune responses to pathogens, substantial research has been carried out with the aim of understanding the function and biological importance of TLRs on immune cells. However, TLRs are also expressed on many kinds of tumors, such as on melanoma, brain tumor and colon tumor cells [4][5][6][7][8]. Preliminary evidence has suggested that TLRs expressed on tumor cells may play an important role in tumor development.…”
Section: Introductionmentioning
confidence: 97%
“…In the case of mantle cell lymphoma, stimulation of TLR4 by LPS promoted tumor growth and played an imparting role in the resistance of cytotoxic T lymphocyte-mediated destruction [67]. MMs also use TLR4 in malignant progression, promoting proliferation in part by the proliferative abilities mediated by IL-6 production, preventing apoptosis and facilitating immune evasion [68,69,70]. To some extent, TLR9 may play a role in such progression as well [68].…”
Section: Toll-like Receptor Signaling and Its Implications In Diseasementioning
confidence: 99%
“…J. Bohnhorst и соавт. [107] обнаружили TLR-опосредованные взаимодействия между ними [108]. Механизмы этой взаимосвязи не до конца понятны, хотя утверждается, что прогрессирование ММ иници-ируется в местах воспаления [109].…”
Section: кумулятивная доля выжившихunclassified
“…Активация TLR опосредует секрецию аутокринного IL-6 стромальными клетками костного мозга. IL-6 является самым важным фактором роста Значение генетических маркеров при ММ и выживания клеток ММ [107,111], участвующим в формировании лекарственной устойчивости [105].…”
Section: кумулятивная доля выжившихunclassified
See 1 more Smart Citation